Home garden coffee as a repository of epiphyte biodiversity in Ethiopia. Issue 10 (1st December 2008) - Hylander, Kristoffer; Nemomissa, Sileshi
Abstract : To mitigate extinction of tropical forest biota, it is becoming increasingly important to focus on the role of agriculture‐dominated landscapes in preserving biodiversity. Previous studies have focused on the importance of native trees for improving forest species conservation in the agroecological matrix, but we show that a cultivated crop (coffee) may also be important. In Ethiopia, coffee's place of origin, home garden coffee shrubs functioned as a substrate for a large number of epiphytic rainforest bryophytes and vascular plants and were of the same or higher importance in terms of harboring forest biota than shade trees in the same system. Our results highlight the potential for shade‐coffee agroecosystems to serve as a conservation and restoration tool for both tree and shrub‐layer biodiversity in densely populated and heavily deforested regions.